A surface treatment method for sintering stainless steel material into embryo

Through polishing process and surface treatment technology, the problem of poor surface smoothness of stainless steel material sintered into embryos is solved, and the material is high smoothness, flatness and brightness are achieved, improving the comfort and safety of use.

CN118385583BActive Publication Date: 2025-03-25ZHONGSHAN SINTS POWDER METALLURGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410514887.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-26
Publication Date
2025-03-25
Estimated Expiration
2044-04-26

AI Technical Summary

Technical Problem

The surface smoothness of the sintered stainless steel material is poor, and there are burrs that affect the flatness and brightness of the material, especially in small-scale processed products and oral applications.

Method used

The embryos are prepared by using 17-4 stainless steel powder and 304 stainless steel powder, and the burrs are removed through the polishing process, combined with the use of brighteners, surface brushing treatment and sealing agents to improve the smoothness, flatness and brightness of the material.

Benefits of technology

Effectively remove burrs, improve the smoothness and flatness of stainless steel materials, enhance brightness, improve the comfort and safety of materials, and improve the corrosion resistance and oxidation resistance of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004813053090000091
    Figure BDA0004813053090000091
Patent Text Reader

Abstract

The present application relates to the field of surface treatment of metal materials, and specifically discloses a surface treatment method for sintering a stainless steel material into an embryo, comprising the following steps: S1, using 17-4 stainless steel powder and 304 stainless steel powder to prepare an embryo; S2, polishing the embryo at a rotation speed of 40-50r / min for 30-35min, adding a brightener during the polishing process, and then washing with water, surface wire drawing treatment, and ultrasonic cleaning, and drying to obtain a semi-finished product; S3, placing the semi-finished product in a sealing agent and soaking it for 10-15min, taking out the semi-finished product, and drying it to obtain a finished stainless steel material; the finished stainless steel material has the advantages of a smooth surface and high brightness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of surface treatment of metal materials, and more specifically, to a surface treatment method for sintered stainless steel materials. Background Art

[0002] Stainless steel is a type of stainless steel with anti-corrosion properties. It is not easy to rust because a strong oxide protective film can be formed on its surface. It has the advantages of high strength and corrosion resistance and is widely used in kitchen utensils, medical equipment, chemical equipment and other fields.

[0003] However, the surface smoothness of the stainless steel blank is poor, and burrs are prone to occur, which affect the flatness and smoothness of the stainless steel surface. Especially when preparing some small processed products, the presence of tiny burrs also has a great impact on their use. For example, the metal brackets used in the process of orthodontic treatment. The presence of burrs in the oral cavity will inevitably affect the comfort of the brackets in the mouth, and in severe cases, it is easy to cause scratches inside the oral cavity. At the same time, the presence of burrs will also affect the brightness of the stainless steel material.

[0004] Therefore, how to prepare a new stainless steel material with the advantages of smooth surface and high brightness is a problem to be solved. Summary of the invention

[0005] In order to prepare a new stainless steel material with the advantages of smooth surface and high brightness, the present application provides a surface treatment method for sintering a stainless steel material into a blank.

[0006] The present application provides a surface treatment method for sintering a stainless steel material into a blank, which adopts the following technical solution:

[0007] A surface treatment method for a stainless steel material sintered into a blank comprises the following steps:

[0008] S1. Using 17-4 stainless steel powder and 304 stainless steel powder to prepare embryos;

[0009] S2, the embryo body is polished at a speed of 40-50r / min for 30-35min, brightener is added during the polishing process, and then washed with water, subjected to surface wire drawing, and then ultrasonically cleaned and dried to obtain a semi-finished product;

[0010] S3. Soak the semi-finished product in the sealant for 10-15 minutes, take out the semi-finished product, and dry it to obtain the finished stainless steel material.

[0011] By adopting the above technical scheme, the burrs prepared by 17-4 stainless steel powder and 304 stainless steel powder are removed by polishing process, and the smoothness and flatness of the surface of the stainless steel material are improved while removing the burrs. In combination with a brightener, the brightness of the finished stainless steel material is improved; the surface wire drawing treatment can make the stainless steel undergo plastic deformation and change the state of the organization and grain boundaries, so that the grain boundaries of the 17-4 stainless steel powder and the 304 stainless steel powder are intertwined and combined with each other, thereby improving the brightness and flatness; and in combination with the immersion treatment of the sealant, the pit positions on the surface of the stainless steel material are further filled, thereby improving the smoothness, flatness and brightness of the stainless steel material.

[0012] Preferably, S1, 17-4 stainless steel powder and 304 stainless steel powder are mixed and stirred evenly to obtain a mixture; a binder is added to the mixture for kneading, and injection molding is performed to obtain a green embryo; the green embryo is degreased, and then sintered at 800-1000° C. for 8-12 hours, and then the temperature is raised to 1150-1350° C. and continued to sinter for 4-6 hours to obtain an embryo body.

[0013] By adopting the above technical solution, after 17-4 stainless steel and 304 stainless steel are mixed, a binder is added for mixing, so that 17-4 stainless steel and 304 stainless steel can be stably bonded, while the contact between stainless steel powders is improved, and the probability of micropores between 17-4 stainless steel and 304 stainless steel during green embryo sintering is reduced, thereby improving the strength and toughness of the stainless steel material; combined with surface wire drawing treatment, the strength and toughness of the stainless steel material are further improved.

[0014] The sintering temperature is limited to ensure the density of the embryonic body structure, thereby improving the strength and toughness of the finished stainless steel material.

[0015] Preferably, the binder is composed of phenolic resin, amino-modified boron nitride, magnesium silicide and ethanol in a mass ratio of 1:0.1-0.3:0.1-0.2:90-100.

[0016] By adopting the above technical scheme, the phenolic resin is dissolved in ethanol, so that the binder has a bonding effect, and the hydroxyl group in the phenolic resin is combined with the amino group of the amino-modified boron nitride to stably bond the amino-modified boron nitride and magnesium silicide on the surface of the mixture, so that the amino-modified boron nitride is intercalated in the stainless steel material; in the degreasing and sintering process, the phenolic resin is gradually carbonized and decomposed as the degreasing and sintering proceed, and although the phenolic resin around the intercalated boron nitride is carbonized, the boron nitride will not be carbonized, thereby reducing the size of the micropore channels generated by the carbonization of the phenolic resin; and the phenolic resin can be completely carbonized at 800-1000°C to generate structural gaps in the embryo, while the melting point of magnesium silicide is about 1100°C, and after sintering, the temperature is finally raised to the melting point of magnesium silicide, so that the magnesium silicide is hot-melted and the micropores are blocked, further improving the structural density of the embryo, thereby improving the strength of the embryo, and combined with the higher toughness of magnesium silicide, the toughness of the embryo is improved, so that the stainless steel material has the advantages of high strength and high toughness.

[0017] Preferably, the brightener comprises the following raw materials in parts by weight: 20-40 parts of sodium hydroxide, 5-10 parts of corn starch, 2-5 parts of sucrose ester, 1-3 parts of sodium lauroyl sarcosinate, 120-180 parts of solvent, and 1-2 parts of fatty alcohol polyoxyethylene ether.

[0018] By adopting the above technical scheme, sodium hydroxide can remove the grease on the surface of the embryo, so that the grease is separated from the embryo surface, and the grease separated from the embryo surface is adsorbed by the adsorption effect of corn starch on the grease, so as to prevent the grease from re-adhering to the embryo surface, thereby improving the removal effect of the grease on the embryo surface; and the grease dispersing effect and emulsifying effect of sucrose ester are combined to facilitate the uniform dispersion of the grease, ensure the contact between the grease and corn starch, and improve the removal effect of the grease; and the hydrophilic end and lipophilic end of the sucrose ester and the dispersing effect of sodium lauroyl amino acid and fatty alcohol polyoxyethylene ether are utilized to facilitate the removal of the grease on the embryo surface, thereby improving the glossiness.

[0019] Preferably, a polishing liquid is added during the polishing process, and the polishing liquid comprises the following raw materials in parts by weight:

[0020] 100-120 parts of water, 3-10 parts of carboxyl-modified diamond particles, 2-8 parts of silane-modified silicon carbide, 5-15 parts of polyethylene glycol, 1-3 parts of sodium dodecylbenzene sulfonate, and 2-5 parts of oxidant.

[0021] By adopting the above technical solution, after the embryo is sintered, the silicon in the magnesium silicide exposed to the outside is easy to attract the silane on the surface of the silane-modified silicon carbide. There are burrs around the location of the magnesium silicide. The overflow of gas during the carbonization process leads to the formation of pores. There is phenolic resin around the magnesium silicide. During the carbonization process, there must be tips and burrs around the gas channel. The silane-modified silicon carbide is polished and polished near the pores. The gloss and surface flatness of the stainless steel material are improved.

[0022] The sucrose ester and fatty alcohol polyoxyethylene ether in the brightener have a bonding effect and are easily bonded to the surface of the mixture. The lipophilic group is attached to the surface of the mixture, and the hydrophilic group faces outward. The carboxyl group in the carboxyl-modified diamond particles in the polishing liquid is easy to contact with the mixture, so that the grease position is ground by the carboxyl-modified diamond particles, which improves the removal effect of lipid substances on the surface of the embryo, thereby improving the polishing efficiency and the smoothness of the surface of the stainless steel material.

[0023] Preferably, the carboxyl-modified diamond particles are prepared by treating diamond particles with citric acid.

[0024] By adopting the above technical solution, carboxyl groups are attached to the surface of the diamond particles after being treated with citric acid, which not only improves the dispersion effect of the diamond particles and facilitates the uniform contact between the diamond particles and the embryo, but also promotes the carboxyl-modified diamond particles to grind and polish the burrs and tip positions near the micropores, thereby improving the brightness and flatness of the finished stainless steel material.

[0025] Preferably, the silane-modified silicon carbide is prepared by treating silicon carbide with a silane coupling agent KH-570.

[0026] By adopting the above technical solution, the silane coupling agent KH-570 has hydrophobicity, which prevents magnesium silicide from absorbing water, and silane is easy to attract silicon in magnesium silicide, promoting the contact between silane-modified silicon carbide and the burrs around the magnesium silicide, and under the polishing effect, the surface flatness and brightness of the stainless steel material are improved.

[0027] Preferably, the sealing agent comprises the following raw materials in parts by weight:

[0028] 70-100 parts of passivation solution, 1-5 parts of cubic alumina, and 1-2 parts of PMMA microspheres.

[0029] By adopting the above technical scheme, the passivation liquid, cubic alumina and PMMA microspheres are matched, and the viscosity of the passivation liquid is utilized to facilitate the cubic alumina and PMMA microspheres to be bonded to the surface of the blank after the wire drawing process. During the wire drawing process, the stainless steel undergoes lattice migration to form a filamentous structure. The cubic alumina utilizes its cubic structure to facilitate filling in the grooves on the surface of the stainless steel, and in combination with the spherical particles of the PMMA microspheres, as the passivation liquid migrates on the surface of the stainless steel material, the PMMA microspheres can be filled in the grooves, thereby improving the smoothness and flatness of the stainless steel surface. At the same time, the refractive and reflective effects of the cubic alumina and the high light transmittance of the PMMA microspheres can be utilized to improve the glossiness of the grooves, thereby improving the brightness and flatness of the surface of the finished stainless steel material.

[0030] In summary, this application has the following beneficial effects:

[0031] 1. The polishing process is used to remove the burrs made of 17-4 stainless steel powder and 304 stainless steel powder. While removing the burrs, the smoothness and flatness of the stainless steel surface are improved. In combination with a brightener, the brightness of the finished stainless steel material is improved; the surface wire drawing treatment can make the stainless steel plastically deformed and change the state of the organization and grain boundaries, so that the grain boundaries of 17-4 stainless steel powder and 304 stainless steel powder are intertwined and combined, thereby improving the brightness and flatness; and in combination with the immersion treatment of the sealant, the pits on the surface of the stainless steel material are further filled, thereby improving the smoothness, flatness and brightness of the stainless steel material.

[0032] 2. When the sintering temperature is between 800 and 1000°C, the carbonization of the phenolic resin is ensured. During the carbonization process, interconnected micropores are generated inside and on the surface of the embryo. When the sintering temperature rises to about 1200°C, magnesium silicide is hot-melted and filled. The pores originally generated by the hot-melting of the phenolic resin are blocked by magnesium silicide, thereby reducing the porosity of the stainless steel surface and improving the strength and toughness of the finished stainless steel.

[0033] 3. Sodium hydroxide can remove grease from the embryo surface, separate the grease from the embryo surface, and combine with the adsorption effect of corn starch on grease to adsorb the grease separated from the embryo surface, prevent the grease from re-adhering to the embryo surface, and improve the removal effect of grease from the embryo surface; and combine with the grease dispersing effect and emulsifying effect of sucrose ester to evenly disperse the grease, ensure the contact between the grease and corn starch, and improve the removal effect of grease; and utilize the hydrophilic end of sucrose ester and the lipophilic end of sucrose ester and the dispersing effect of sodium lauroyl amino acid and fatty alcohol polyoxyethylene ether to remove grease from the embryo surface, thereby improving the glossiness.

[0034] 4. Limit the immersion time of the sealant so that the sealant adheres to the surface of the stainless steel material, thereby improving the corrosion resistance, strength and oxidation resistance of the stainless steel material, and also improving the smoothness of the stainless steel surface. DETAILED DESCRIPTION

[0035] The present application is further described in detail below with reference to the embodiments.

[0036] Preparation Example of Amino-modified Boron Nitride

[0037] Among the following raw materials, polydopamine was purchased from hydroxypolyethylene glycol dopamine produced by Shanghai Tuoyang Biotechnology Co., Ltd.; other raw materials and equipment used were all commercially available.

[0038] Preparation Example 1: Amino-modified boron nitride is prepared by the following method:

[0039] 1 kg of boron nitride was weighed and uniformly dispersed in 10 kg of polydopamine solution, the polydopamine solution was a polydopamine aqueous solution with a mass fraction of 2%, dispersed for 10 minutes under 20 kHz conditions, and the boron nitride was filtered and separated to obtain a finished amino-modified boron nitride, which was cubic boron nitride; the average particle size of the amino-modified boron nitride was 3 μm.

[0040] Preparation example of adhesive

[0041] Preparation Example 2: The binder is prepared by the following method:

[0042] 1 kg of phenolic resin was weighed and placed in 100 kg of ethanol and stirred until the phenolic resin was completely dissolved, with the mass fraction of ethanol being 95%, to obtain a phenolic resin solution; then, 0.3 kg of amino-modified boron nitride prepared in Preparation Example 1 and 0.2 kg of magnesium silicide were added, the average particle size of the magnesium silicide was 5 μm, and the addition rate of the amino-modified boron nitride and magnesium silicide was 60 g / min. During the addition process, the phenolic resin was stirred at a speed of 120 r / min. After being evenly mixed, a finished adhesive solution was obtained.

[0043] Preparation Example 3: This preparation example differs from Preparation Example 2 in that:

[0044] 1 kg of phenolic resin was weighed and placed in 100 kg of ethanol and stirred until the phenolic resin was completely dissolved to obtain a phenolic resin solution; then 0.1 kg of amino-modified boron nitride prepared in Preparation Example 1 and 0.1 kg of magnesium silicide were added, the average particle size of the magnesium silicide was 5 μm, and the addition rate of the amino-modified boron nitride and magnesium silicide was 60 g / min. During the addition process, the phenolic resin was stirred at a speed of 120 r / min. After mixing evenly, a finished adhesive solution was obtained.

[0045] Preparation example of brightener

[0046] Among the following raw materials, sodium lauroyl sarcosinate was purchased from Shandong Guohua Chemical Co., Ltd.; fatty alcohol polyoxyethylene ether was purchased from Hai'an Petrochemical Plant, Jiangsu Province; sucrose ester was purchased from sucrose fatty acid ester produced by Shaanxi Chenming Biotechnology Co., Ltd.; other raw materials were all commercially available.

[0047] Preparation Example 4: Brightener is prepared by the following method:

[0048] Weigh 30kg of sodium hydroxide, 8kg of corn starch, 4kg of sucrose ester, 2kg of sodium lauroyl sarcosinate, 150kg of solvent, and 1kg of fatty alcohol polyoxyethylene ether for later use; the solvent is water;

[0049] Sodium hydroxide and solvent are mixed and stirred evenly, and then corn starch is added and stirred evenly. After sucrose ester, sodium lauroyl sarcosinate and fatty alcohol polyoxyethylene ether are added and mixed, the temperature is controlled to 60° C. and stirred for 10 minutes to obtain a brightener.

[0050] Preparation Example 5: This preparation example differs from Preparation Example 4 in that:

[0051] Weigh 20 kg of sodium hydroxide, 5 kg of corn starch, 2 kg of sucrose ester, 1 kg of sodium lauroyl sarcosinate, 120 kg of solvent, and 1 kg of fatty alcohol polyoxyethylene ether for use.

[0052] Preparation Example 6: This preparation example differs from Preparation Example 4 in that:

[0053] Weigh 40 kg of sodium hydroxide, 10 kg of corn starch, 5 kg of sucrose ester, 3 kg of sodium lauroyl sarcosinate, 180 kg of solvent, and 2 kg of fatty alcohol polyoxyethylene ether for later use;

[0054] Preparation example of polishing liquid

[0055] The following raw materials are all commercially available.

[0056] Preparation Example 7: The polishing liquid is prepared by the following method:

[0057] 1 kg of diamond particles are placed in 10 kg of citric acid solution, stirred and dispersed at a speed of 1000 r / min for 20 minutes, and then the diamond particles are filtered out to obtain carboxyl-modified diamond particles; the average particle size of the diamond particles is 10 μm, and the citric acid solution is a citric acid aqueous solution with a mass fraction of 10%;

[0058] 1 kg of silicon carbide was placed in 9 kg of silane coupling agent KH-570, and the mixture was stirred and dispersed at a speed of 2000 r / min for 20 minutes, and the average particle size of the silicon carbide was 5 μm. The silicon carbide was then separated and filtered to obtain silane-modified silicon carbide.

[0059] Weigh 110 kg of water, 8 kg of carboxyl-modified diamond particles, and 5 kg of silane-modified silicon carbide, and mix them evenly. Then add 10 kg of polyethylene glycol, 2 kg of sodium dodecylbenzene sulfonate, and 3 kg of antioxidant, and mix them evenly. The polyethylene glycol is polyethylene glycol 8000, and the antioxidant is antioxidant 1010, to obtain a finished polishing liquid.

[0060] Preparation Example 8: This preparation example differs from Preparation Example 7 in that:

[0061] Weigh 100 kg of water, 5 kg of carboxyl-modified diamond particles, and 2 kg of silane-modified silicon carbide, mix and stir evenly, then add 5 kg of polyethylene glycol, 1 kg of sodium dodecylbenzene sulfonate, and 2 kg of oxidant, mix and stir evenly to obtain a finished polishing liquid.

[0062] Preparation Example 9: This preparation example differs from Preparation Example 7 in that:

[0063] Weigh 120 kg of water, 10 kg of carboxyl-modified diamond particles, and 8 kg of silane-modified silicon carbide, mix and stir evenly, then add 15 kg of polyethylene glycol, 3 kg of sodium dodecylbenzene sulfonate, and 5 kg of oxidant, mix and stir evenly to obtain a finished polishing liquid.

[0064] Preparation example of blocking agent

[0065] The passivation solution in the following raw materials was purchased from Shenzhen DunHua Technology Co., Ltd., model: DunHua 968; other raw materials are all commercially available.

[0066] Preparation Example 10: The sealing agent is prepared by the following method:

[0067] Add 3kg of cubic alumina and 2kg of PMMA microspheres to 90kg of passivation liquid. The adding rate of cubic alumina and PMMA microspheres is 30g / min. During the adding process, the stirring speed of the passivation liquid is 300r / min. The average particle size of the cubic alumina is 60nm, and the average particle size of the PMMA microspheres is 40nm. Mix and stir evenly to obtain a finished polishing liquid.

[0068] Preparation Example 11: This preparation example differs from Preparation Example 10 in that:

[0069] Add 1kg of cubic alumina and 1kg of PMMA microspheres to 70kg of passivation liquid. The adding rate of cubic alumina and PMMA microspheres is 30g / min. During the adding process, the stirring speed of the passivation liquid is 300r / min. The average particle size of the cubic alumina is 60nm, and the average particle size of the PMMA microspheres is 40nm. Mix and stir evenly to obtain a finished polishing liquid.

[0070] Preparation Example 12: This preparation example differs from Preparation Example 10 in that:

[0071] Add 5kg of cubic alumina and 2kg of PMMA microspheres to 100kg of passivation liquid. The adding rate of cubic alumina and PMMA microspheres is 30g / min. During the adding process, the stirring speed of the passivation liquid is 300r / min. The average particle size of the cubic alumina is 60nm, and the average particle size of the PMMA microspheres is 40nm. Mix and stir evenly to obtain a finished polishing liquid.

[0072] Example

[0073] The 17-4 stainless steel powder and 304 stainless steel powder in the following raw materials were purchased from Qinghe County Yinghe Metal Materials Co., Ltd.; the commercially available brightener was purchased from Zhongshan Yicheng Polishing Equipment Co., Ltd., model: 870 polishing liquid.

[0074] Example 1: A surface treatment method for sintering a stainless steel material into a blank:

[0075] S1. Mix 17-4 stainless steel powder and 304 stainless steel powder and stir them evenly to obtain a mixture; add the binder prepared in Preparation Example 2 to the mixture and mix them, the mixing speed is 120r / min, the mixing temperature is 150°C, the mixing time is 60min, the mass ratio of the mixture to the binder is 1:0.4, and the binder is the binder prepared in Preparation Example 2; injection molding is performed, the injection temperature is 120°C, the injection pressure is 130MPa, the holding pressure is 100MPa, and the holding time is 10s to obtain a green embryo; the green embryo is degreased at 700°C for 5h, then sintered at 900°C for 10h to complete carbonization, and finally sintered at 1200°C for 2h, and after cooling, an embryo body is obtained;

[0076] S2, the embryo body is subjected to magnetic polishing, wherein the polishing liquid prepared in Preparation Example 7 is selected as the polishing liquid, and the brightener prepared in Preparation Example 4 is added during the polishing process, the mass ratio of the polishing liquid to the brightener is 1:0.1, the rotation speed during the polishing process is 50r / min, the polishing time is 30min, and then washed with water twice, dried, and then subjected to surface drawing by a stainless steel surface drawing machine, and then ultrasonically cleaned for 10min under 20kHz conditions, and dried to obtain a semi-finished product;

[0077] S3. The semi-finished product is placed in the sealant prepared in Preparation Example 10 and allowed to soak for 15 minutes. The semi-finished product is then taken out and air-dried to obtain a finished stainless steel material.

[0078] Embodiment 2: This embodiment differs from Embodiment 1 in that:

[0079] S1. Mix 17-4 stainless steel powder and 304 stainless steel powder and stir evenly to obtain a mixture; add a binder to the mixture and mix it, the binder is the binder prepared in Preparation Example 3, and inject it to obtain a green embryo; the green embryo is degreased at 700° C. for 5 h, then sintered at 800° C. for 12 h to complete carbonization, and finally sintered at 1150° C. for 6 h, and after cooling, a embryo body is obtained;

[0080] S2, the embryo body is subjected to magnetic polishing, wherein the polishing liquid prepared in Preparation Example 8 is selected as the polishing liquid, a commercially available brightener is added during the polishing process, the mass ratio of the polishing liquid to the brightener is 1:0.1, the rotation speed during the polishing process is 40r / min, the polishing time is 35min, and then washed with water twice, dried, and then subjected to surface drawing by a stainless steel surface drawing machine, and then ultrasonically cleaned for 10min under 20kHz conditions to obtain a semi-finished product;

[0081] S3. The semi-finished product is placed in the sealant prepared in Preparation Example 11 and allowed to soak for 10 minutes. The semi-finished product is then taken out and air-dried to obtain a finished stainless steel material.

[0082] Embodiment 3: This embodiment differs from Embodiment 1 in that:

[0083] S1. Mix 17-4 stainless steel powder and 304 stainless steel powder and stir evenly to obtain a mixture; add a binder to the mixture and mix it, the binder is the binder prepared in Preparation Example 2, and inject it to obtain a green embryo; the green embryo is degreased at 700° C. for 5 h, then sintered at 1000° C. for 8 h to complete carbonization, and finally sintered at 1350° C. for 4 h, and after cooling, a embryo body is obtained;

[0084] S2, the embryo body is subjected to magnetic polishing, wherein the polishing liquid prepared in Preparation Example 9 is selected as the polishing liquid, and the brightener prepared in Preparation Example 6 is added during the polishing process, the mass ratio of the polishing liquid to the brightener is 1:0.1, the rotation speed during the polishing process is 50r / min, the polishing time is 35min, and then washed with water twice, after drying, the surface is drawn by a stainless steel surface drawing machine, and then ultrasonically cleaned for 10min under 20kHz to obtain a semi-finished product;

[0085] S3. The semi-finished product is placed in the sealant prepared in Preparation Example 12 and allowed to soak for 15 minutes. The semi-finished product is then taken out and air-dried to obtain a finished stainless steel material.

[0086] Embodiment 4: This embodiment differs from Embodiment 1 in that:

[0087] No magnesium silicide was added to the binder.

[0088] Embodiment 5: This embodiment differs from Embodiment 1 in that:

[0089] No amino-modified boron nitride was added to the binder.

[0090] Embodiment 6: This embodiment differs from Embodiment 1 in that:

[0091] Replace the sodium hydroxide in the brightener with an equal mass of hydrochloric acid.

[0092] Embodiment 7: This embodiment differs from Embodiment 1 in that:

[0093] No corn starch or sucrose esters are added to the brightener.

[0094] Embodiment 8: This embodiment differs from Embodiment 1 in that:

[0095] In the polishing liquid, the carboxyl-modified diamond is replaced by the diamond of the same mass, and the silane-modified silicon carbide is replaced by the silicon carbide of the same mass.

[0096] Embodiment 9: This embodiment differs from Embodiment 1 in that:

[0097] Cubic alumina and PMMA microspheres were not added to the sealant.

[0098] Comparative Example

[0099] Comparative Example 1: The difference between this comparative example and Example 1 is that:

[0100] No surface brushing was performed in S2.

[0101] Performance testing

[0102] 1. Density detection

[0103] Finished stainless steel materials were prepared by the preparation methods of Examples 1-6 respectively, and the density was tested according to the Archimedes drainage method, and the data was recorded.

[0104] 2. Strength detection

[0105] Finished stainless steel materials were prepared by the preparation methods of Examples 1-6 and 9, respectively. The tensile strength was tested according to ASTM E381-2001, and the elongation was tested according to GB 18457-2015, and the data were recorded.

[0106] 3. Roughness detection

[0107] Finished stainless steel materials were prepared by the preparation methods of Examples 1-3, 7-9 and Comparative Example 1, respectively, and the surface roughness of the stainless steel materials was tested and the data was recorded.

[0108] 4. Glossiness detection

[0109] Finished stainless steel materials were prepared by the preparation methods of Examples 1-3, 7-9 and Comparative Example 1, respectively, and the surface glossiness was tested by a micro gloss meter A-4430 (BYK, Germany).

[0110] 5. Brightness detection

[0111] Finished stainless steel materials were prepared using the preparation methods of Examples 1-3, 7-9 and Comparative Example 1, and their surface brightness was rated:

[0112] The rating criteria are as follows:

[0113] Level 1: There is a white film on the surface, but no brightness; Level 2: It is slightly bright and the outline cannot be seen clearly; Level 3: The brightness is good and the outline can be seen; Level 4: The surface is bright and the outline can be seen clearly; Level 5: It is as bright as a mirror.

[0114] Table 1 Performance test table (the " / " in the following table represents the corresponding embodiment or comparative example. The item was not tested, so there is no data)

[0115]

[0116] It can be seen from Examples 1-3 and Table 1 that the stainless steel material prepared in the present application has the advantages of high density, high strength, high toughness, and low roughness, indicating high smoothness, and high gloss and brightness.

[0117] Combining Example 1 and Examples 4-9 and Table 1, it can be seen that magnesium silicide is not added to the binder in Example 4. Compared with Example 1, the density of the stainless steel material prepared in Example 4 is lower than that in Example 1, and the tensile strength and elongation are lower than those in Example 1; this indicates that in the process of carbonization sintering, the carbonization of substances such as phenolic resin is first ensured, and then the temperature is increased to ensure the hot melting of magnesium silicide, and the micropores generated by carbonization are bonded, thereby improving the density and strength of the finished stainless steel material, and the toughness of magnesium silicide can also be used to improve the toughness of the stainless steel material.

[0118] In Example 5, amino-modified boron nitride is not added to the binder. Compared with Example 1, the density of the stainless steel material prepared in Example 5 is lower than that in Example 1, and the tensile strength is lower than that in Example 1. This indicates that the addition of amino-modified boron nitride can be filled in the embryo structure, and the surface of the amino-modified boron nitride is bonded with the phenolic resin. As the phenolic resin is carbonized, the boron nitride will not be carbonized, so that the size of the micropores generated by the carbonization of the phenolic resin is reduced. If there is no amino-modified boron nitride, only the phenolic resin exists. As the phenolic resin is carbonized, all the phenolic resin filling positions are micropores, which increases the size of the micropores. Therefore, amino-modified boron nitride can improve the structural density and strength of the finished stainless steel material.

[0119] In Example 6, the sodium hydroxide is replaced by an equal mass of hydrochloric acid in the brightener. Compared with Example 1, the density of the stainless steel material prepared in Example 6 is lower than that in Example 1, and the tensile strength is lower than that in Example 1; this indicates that hydrochloric acid reacts with magnesium silicide, and magnesium silicide is stable in alkaline solution. Therefore, when hydrochloric acid dissolves magnesium silicide, the microporosity and micropore size of the stainless steel material are increased, thereby affecting the strength of the stainless steel material.

[0120] No corn starch and sucrose ester were added to the brightener of Example 7. Compared with Example 1, the stainless steel material prepared in Example 7 had a roughness greater than that of Example 1, a glossiness lower than that of Example 1, and a brightness rating worse than that of Example 1. This indicates that the addition of corn starch and sucrose ester facilitates the removal of grease and other impurities on the surface of the embryo, and ensures the glossiness and surface smoothness of the finished stainless steel material.

[0121] In the polishing liquid of Example 8, the carboxyl-modified diamond is replaced by diamond of equal mass, and the silane-modified silicon carbide is replaced by silicon carbide of equal mass. Compared with Example 1, the stainless steel material prepared in Example 8 has a roughness greater than that in Example 1, a glossiness lower than that in Example 1, and a brightness rating worse than that in Example 1, which indicates that carboxyl-modified diamond and silane-modified silicon carbide can not only improve the polishing efficiency, but also improve the surface flatness and brightness of the finished stainless steel material.

[0122] Cubic alumina and PMMA microspheres were not added to the sealant of Example 9. Compared with Example 1, the strength of the stainless steel material prepared in Example 9 was lower than that in Example 1, the roughness was greater than that in Example 1, the glossiness was lower than that in Example 1, and the brightness rating was worse than that in Example 1; this indicates that cubic alumina and PMMA microspheres have a higher light refraction effect, and can improve the glossiness of the finished stainless steel material while filling the grooves.

[0123] Combining Example 1 and Comparative Example 1 and Table 1, it can be seen that the stainless steel material of Comparative Example 1 was not subjected to surface brushing during the preparation process. Compared with Example 1, the stainless steel material prepared in Comparative Example 1 has a roughness greater than that of Example 1, a glossiness less than that of Example 1, and a brightness rating worse than that of Example 1; this indicates that surface brushing can improve the surface flatness and gloss of the stainless steel material, thereby improving the aesthetics of the stainless steel material.

[0124] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A surface treatment method for sintering stainless steel material into embryos, characterized in that: The steps include: S1. Mix 17-4 stainless steel powder and 304 stainless steel powder and stir them evenly to obtain a mixture; add a binder to the mixture and mix them, and then obtain a green embryo by injection molding; the green embryo is degreased, and then sintered at 800-1000° C. for 8-12 hours, and then heated to 1150-1350° C. and continued to sinter for 4-6 hours to obtain an embryo body; the binder is composed of phenolic resin, amino-modified boron nitride, magnesium silicide and ethanol in a mass ratio of 1:0.1-0.3:0.1-0.2:90-100; S2, the embryo body is polished at a speed of 40-50r / min for 30-35min, a brightener is added during the polishing process, and then the semi-finished product is obtained after water washing, surface wire drawing treatment, ultrasonic cleaning, and drying; the brightener comprises the following raw materials in parts by weight: 20-40 parts of sodium hydroxide, 5-10 parts of corn starch, 2-5 parts of sucrose ester, 1-3 parts of sodium lauroyl sarcosinate, 120-180 parts of solvent, and 1-2 parts of fatty alcohol polyoxyethylene ether; polishing liquid is added during the polishing process, and the polishing liquid comprises the following raw materials in parts by weight: 100-120 parts of water, 5-10 parts of carboxyl-modified diamond particles, 2-8 parts of silane-modified silicon carbide, 5-15 parts of polyethylene glycol, 1-3 parts of sodium dodecylbenzene sulfonate, and 2-5 parts of an oxidant; S3. Soak the semi-finished product in a sealant for 10-15 minutes, take out the semi-finished product, and dry it to obtain a finished stainless steel material; the sealant contains the following raw materials in parts by weight: 70-100 parts of passivation solution, 1-5 parts of cubic alumina, and 1-2 parts of PMMA microspheres.

2. The surface treatment method for sintered stainless steel material according to claim 1, characterized in that: The carboxyl modified diamond particles are prepared by treating diamond particles with citric acid.

3. The surface treatment method for sintered stainless steel material according to claim 1, characterized in that: The silane-modified silicon carbide is prepared by treating silicon carbide with a silane coupling agent KH-570.

Citation Information

Patent Citations

  • Manufacturing method for dental high-speed handpiece head

    CN107020381A